Efektivitas Hybrid Learning Pada Mata Pelajaran Sejarah Di SMAN 4 Kota Serang T.A 2021/2022 - Rusli Hadi; Eko Ribawati; Moh Ali Fadillah (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study aims to determine the effectiveness of using Hybrid Learning in history subjects in class X IPA 6 and X IPS 3. The method used in this study is a qualitative descriptive method with a case study approach. The instrument used in this study was a closed questionnaire which was distributed to students in class X IPA 6 and X IPS 3 at SMAN 4 Serang City via Google Forms. The results of this study show: (1) history learning carried out at SMAN 4 Serang Serang City after the pandemic was carried out by applying the Hybrid Learning learning model, the Hybrid Learning learning model is learning with an online or online system combined with face-to-face meetings for several hours, learning carried out in rotation with 50% of students, namely students participating in online learning or face-to-face learning alternately (2) the effectiveness of the application of the hybrid learning model in history learning which is carried out face-to-face can attract students' interest in learning, where face-to-face learning, students can directly interact with teachers, establishing good learning communication between teachers and students so as to make students active in the learning process (3) factors that influence the implementation of the Hybrid Learning model, namely because it is not certain when the pandemic will end While learning activities must be carried out, however, when online learning, there are many obstacles that occur, such as: lack of interaction between teachers and students or students and students, lack of learning tools that support the online learning process, learning is monotonous and makes students passive in learning activities.